Detective Fiction: From its Apocryphal Origins to its Emergence in the 20th Century (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
In popular fiction,  Tony Bennett reflects on the lack of attention in the numerous studies on crime fiction to the relationship between the genre and the ideology and which it is based. Much has been said and written about the characteristic elements and origins of the form and about the best-known authors and works. As a genre it is defended or reviled,  but little has been done to explain why many critics can give it a precise date of origin, the publication in 1841 of Poe’s “The Murders in the Rue  Morgue”. This story combines many of the distinctive elements of crime fiction that had appeared in a scattered way throughout the history of literature,  but here they are used to support one aim:  the exaltation of the central figure of the  Detective as the embodiment of the ideals of a society that believes it can perfect itself. It is thus worthwhile investigating the specific elements of detective fiction of detective fiction by tracing they are progressive configuration towards a systematic arrangement on the disciplined map of the detective world.